Treatability Studies on Organized Industrial District Wastewater with Chemical Treatment, Fenton and Fenton-Like Processes - Yalili Kilic, Melike (Asian Journal of Chemistry, 2013)
Organized industrial districts are established to carry out the industrialization by minimizing the environmental problems. For this reason, wastewater arises from different industries are treated by various treatment processes. In this study, the wastewater of organized industrial district which is situated in Bursa city of Demirtas district, Turkey is treated by chemical treatment with various coagulants and Fenton and Fenton-like processes. Al2(SO4)3·18H2O, FeSO4·7H2O and FeCl3·6H2O were used in chemical treatment studies and 72, 78 and 78 % COD removal, 59, 41 and 50 % suspended solid removal were obtained, respectively. Fenton and Fenton-like processes showed high COD (> 60 %) and suspended solid (> 75 %) removal performance on evaluated effluents.